Association between PM2.5 and risk of hospitalization for myocardial infarction: a systematic review and a meta-analysis - Zeynab Farhadi; Hasan Abulghasem Gorgi; Hosein Shabaninejad; Mouloud Aghajani Delavar; Sogand Torani (BMC, 2020)
Abstract Background It is generally assumed that there have been mixed results in the literature regarding the association between ambient particulate matter (PM) and myocardial infarction (MI). The aim of this meta-analysis was to explore the rate of short-term exposure PM with aerodynamic diameters ≤2.5 μm (PM2.5) and examine its potential effect(s) on the risk of MI. Methods A systematic search was conducted on databases like PubMed, Scopus, Web of Science, and Embase with components: "air pollution" and "myocardial infarction". The summary relative risk (RR) and 95% confidence intervals (95%CI) were also calculated to assess the association between the PM2.5 and MI. Results Twenty-six published studies were ultimately identified as eligible candidates for the meta-analysis of MI until Jun 1, 2018. The results illustrated that a 10-μg/m 3 increase in PM2.5 was associated with the risk of MI (RR = 1.02; 95% CI 1.01-1.03; P ≤ 0.0001). The heterogeneity of the studies was assessed through a random-effects model with p < 0.0001 and the I2 was 69.52%, indicating a moderate degree of heterogeneity. We also conducted subgroup analyses including study quality, study design, and study period. Accordingly, it was found that subgroups time series study design and high study period could substantially decrease heterogeneity (I2 = 41.61, 41.78). Conclusions This meta-analysis indicated that exposure - response between PM2.5 and MI. It is vital decision makers implement effective strategies to help improve air pollution, especially in developing countries or prevent exposure to PM2.5 to protect human health.